Anda di halaman 1dari 6

# Anexo D

Tabla de Integrales
(PUEDE SUMARSE UNA CONSTANTE ARBITRARIA A CADA INTEGRAL)

Z
1
1. xn dx = xn+1 (n 6= −1)
n+1
Z
1
2. dx = log | x |
x
Z
3. ex dx = ex
Z
ax
4. ax dx =
log a
Z
5. sen x dx = − cos x
Z
6. cos x dx = sen x
Z
7. tan x dx = − log |cos x|
Z
8. cot x dx = log |sen x|

Z ¯ µ ¶¯
¯ 1 1 ¯
9. sec x dx = log |sec x + tan x| = log ¯¯tan x + π ¯¯
2 4

227
228 Tabla de Integrales

Z ¯ ¯
¯ 1 ¯¯
10. ¯
csc x dx = log |csc x − cot x| = log ¯tan x¯
2
Z
x x √ 2
11. arcsen dx = x arcsen + a − x2 (a > 0)
a a
Z
x x √
12. arccos dx = x arccos − a2 − x2 (a > 0)
a a
Z
x x a ¡ ¢
13. arctan dx = x arctan − log a2 + x2 (a > 0)
a a 2
Z
1
14. sen2 mx dx = (mx − sen mx cos mx)
2m
Z
1
15. cos2 mx dx = (mx + sen mx cos mx)
2m
Z
16. sec2 x dx = tan x
Z
17. csc2 x dx = −cot x
Z Z
n senn−1 x cos x n − 1
18. sen x dx = − + senn−2 x dx
n n
Z Z
n cosn−1 x sen x n − 1
19. cos x dx = + cosn−2 x dx
n n
Z Z
n tann−1 x
20. tan x dx = − tann−2 x dx (n 6= 1)
n−1
Z Z
n cotn−1 x
21. cot x dx = − cotn−2 x dx (n 6= 1)
n−1
Z Z
n tan x secn−2 x n − 2
22. sec x dx = + secn−2 x dx (n 6= 1)
n−1 n−1
Z Z
n cot x csc n−1 x n − 2
23. csc x dx = + cscn−2 x dx (n 6= 1)
n−2 n−1
Z
24. senh x dx = cosh x
Z
25. cosh x dx = senh x
229

Z
26. tanh x dx = log |cosh x|
Z
27. coth x dx = log |sen hx|
Z
28. sech x dx = arctan (senh x)
Z ¯
¯ x ¯¯ 1 cosh x + 1
29. csch x dx = log ¯tanh ¯ = − log
2 2 cosh x − 1
Z
1 1
30. senh2 x dx = senh 2x − x
4 2
Z
1 1
31. cosh2 x dx = senh 2x + x
4 2
Z
32. sech2 x dx = tanh x
Z
x x √
33. senh−1 dx = xsenh−1 − x2 − a2 (a > 0)
a a
Z ½ √ £ ¡ ¢ ¤
−1 x xcosh−1 xa − √x2 − a2 £cosh−1 ¡ xa ¢ > 0, a > 0¤
34. cosh dx =
a xcosh−1 xa + x2 − a2 cosh−1 xa < 0, a > 0
Z
x x a ¯ ¯
35. tanh−1 dx = xtanh−1 + log ¯a2 − x2 ¯
a a 2
Z ³ √ ´
1 x
36. √ dx = log x + a2 + x2 = sen h−1 (a > 0)
a2 + x2 a
Z
1 1 x
37. 2 2
dx = arctan (a > 0)
a +x 2 a
Z √
x√ 2 a2 x
38. a2 − x2 dx = a − x2 + arcsen (a > 0)
2 2 a
Z
¡ 2 ¢3 x¡ 2 ¢√ 3a4 x
39. a − x2 2 dx = 5a − 2x2 a 2 − x2 + arcsen (a > 0)
8 8 a
Z
1 x
40. √ dx = arcsen (a > 0)
a2 − x2 a
Z ¯ ¯
1 1 ¯a + x¯
41. dx = log ¯¯ ¯
a2 − x2 2a a − x¯
230 Tabla de Integrales

Z
1 x
42. 3 dx = √
(a2 − x2 ) 2 a2 a2 − x2
Z √ ¯ ¯
x√ 2 a2 ¯ √ ¯
43. x2
± dx = a2 2
x ± a ± log ¯x + x ± a ¯2 2
2 2
Z ¯ √ ¯
1 ¯ ¯ x
44. √ dx = log ¯x + x2 − a2 ¯ = cosh−1 (a > 0)
x2 − a 2 a
Z ¯ ¯
1 1 ¯ x ¯
45. dx = log ¯ ¯ ¯
x(a + bx) a a + bx ¯
Z √
3
2 (3bx − 2a) (a + bx) 2
46. x a + bx dx =
15b2
Z √ √ Z
a + bx 1
47. dx = 2 a + bx + a √ dx
x x a + bx
Z √
x 2 (bx − 2a) a + bx
48. √ dx =
a + bx 3b2
 ¯√ ¯
Z  ¯ a+bx−√
√1 log ¯ √

1 a a+bx+
√ ¯ (a > 0)
49. √ dx = q a
x a + bx  √2 arctan a+bx (a > 0)
−a −a

Z √ √
¯ √ ¯
a2 − x2 ¯ a + a2 − x2 ¯
50. dx = a2 − x2 − a log ¯¯ ¯
¯
x x
Z √ 1¡ ¢3
51. x a2 − x2 dx = − a2 − x2 2
3
Z √ x¡ 2 ¢√ a4 x
52. x2 a2 − x2 dx = 2x − a2 a2 − x2 + arcsen (a > 0)
8 8 a
Z ¯ √ ¯
1 1 ¯ a + a 2 − x2 ¯
53. √ dx = − log ¯ ¯ ¯
x a2 − x2 a x ¯
Z √
x
54. √ dx = − a2 − x2
a2 − x2
Z
x2 x√ 2 a2 x
55. √ dx = − a − x2 + arcsen (a > 0)
2
a −x 2 2 2 a
Z √ 2 ¯ ¯
x + a2 √ ¯ a + √x2 + a2 ¯
¯ ¯
56. dx = x2 + a2 − a log ¯ ¯
x ¯ x ¯
231

Z √ √ √ ³x´
x2 − a 2 a
57. dx = x2 − a2 − a arccos = x2 − a2 − arcsec (a > 0)
x |x| a
Z√ 1¡ 2 ¢3
58. x x2 ± a2 dx = x ± a2 2
3
Z ¯ ¯
1 1 ¯ x ¯
59. √ dx = log ¯¯ √ ¯
x x2 + a2 a a + x2 + a2 ¯
Z
1 1 a
60. √ dx = arccos (a > 0)
x x2 − a 2 a |x|
Z √
1 x2 ± a2
61. √ dx = ±
x2 x2 ± a2 a2 x
Z √
x
62. √ dx = x2 ± a2
x2 ± a 2
Z ( ¯ √ ¯
√ 1
¯ 2ax+b−√ b2 −4ac ¯
1 b2 −4ac
log ¯ 2ax+b+ b2 −4ac
¯ (b2 > 4ac)
63. dx =
ax2 + bx + c √ 2 arctan √2ax+b (b2 < 4ac)
4ac−b2 4ac−b2
Z Z
x 1 ¯ 2 ¯ b 1
64. dx = ¯
log ax + bx + c − ¯ dx
2
ax + bx + c 2a 2a 2
ax + bx + c
Z ( √ √
1 √1 log |2ax + b + 2 a ax2 + bx + c| (a > 0)
a
65. √ dx =
ax2 + bx + c √1 arcsen √ −2ax−b
(a < 0)
−a b2 −4ac
Z √ Z
2ax + b √ 2 4ac − b2 1
66. ax2
+ bx + c dx = ax + bx + c + √ dx
4a 8a ax2 + b + c
Z √ Z
x ax2 + bx + c b 1
67. √ dx = − √ dx
2
ax + bx + c a 2a 2
ax + bx + c
( ¯ √√ 2 ¯
Z −1 ¯ 2 c ax +bx+c+bx+2c ¯
1 √
c
log ¯ x ¯ (c > 0)
68. √ dx =
x ax2 + bx + c √1 arcsen bx+2c
√ (c < 0)
−c |x| b2 −4ac
Z µ ¶q
√ 1 2 2 2
69. x 3
x2
+ dx = a2 x − a (a2 + x2 )3
5 15
q
Z √ 2 2 ∓ (x2 ± a2 )3
x ±a
70. dx =
x4 3a2 x3
Z
sen(a − b)x sen(a + b)x ¡ ¢
71. sen ax sen bx dx = − a2 6= b2
2(a − b) 2(a + b)
232 Tabla de Integrales

Z
cos(a − b)x cos(a + b)x ¡ ¢
72. sen ax cos bx dx = − a2 6= b2
2(a − b) 2(a + b)
Z
sen(a − b)x sen(a + b)x ¡ ¢
73. cos ax cos bx dx = − a2 6= b2
2(a − b) 2(a + b)
Z
74. sec x tan x dx = sec x
Z
75. csc x cot x dx = −csc x
Z Z
m n cosm−1 x senn−1 +x m − 1
cos x sen x dx = + cosm−2 x senn x dx =
76. m+n m+nZ
senn−1 x cosm+1 x n−1
= − + cosm x senn−2 x dx
m+n m+n
Z Z
n 1 n n
77. x sen ax dx = − x cos ax + xn−1 cos ax dx
a a
Z Z
n 1 n n
78. x cos ax dx = x sen ax − xn−1 sen ax dx
a a
Z Z
n ax xn eax n
79. x e dx = − xn−1 eax dx
a a
Z · ¸
n n+1 log ax 1
80. x log(ax) dx = x −
n+1 (n + 1)2
Z Z
m xn+1 m m
81. n
x (log ax) dx = (log ax) − xn (log ax)m−1 dx
n+1 n+1
Z
eax (a sen bx − b cos bx)
82. eax sen bx dx =
a2 + b2
Z
eax (b sen bx + a cos bx)
83. eax cos bx dx =
a 2 + b2
Z
84. sech x tanh x dx = −sech x
Z
85. csch x coth x dx = −csch x